Cup-ling oskar RNA localization and translational control. - Lasko, P. (Journal of Cell Biology, 2003)
RNA localization and spatially restricted translational control can serve to deploy specific proteins to particular places within a cell. oskar (osk) RNA is a key initiatior of posterior patterning and germ cell specification in Drosophila, and its localization and translation are under elaborate control. In this issue, Wilhelm et al. (2003) show that the protein Cup both promotes osk localization and participates in repressing translation of unlocalized osk.